In silico epitope analysis of unique and membrane associated proteins from Mycobacterium avium subsp. paratuberculosis for immunogenicity and vaccine evaluation. (7th November 2015) - Carlos, Perla; Roupie, Virginie; Holbert, Sébastien; Ascencio, Felipe; Huygen, Kris; Gomez-Anduro, Gracia; Branger, Maxime; Reyes-Becerril, Martha; Angulo, Carlos
Abstract: Mycobacterium avium subsp. paratuberculosis (MAP) is the etiologic agent of paratuberculosis disease affecting ruminants worldwide. The aim of this study was to identify potential candidate antigens and epitopes by bio and immuno-informatic tools which could be later evaluated as vaccines and/or diagnosis. 110 protein sequences were selected from MAP K-10 genome database: 48 classified as putative enzymes involved in surface polysaccharide and lipopolysaccharide synthesis, as membrane associated and secreted proteins, 32 as conserved membrane proteins, and 30 as absent from other mycobacterial genomes. These 110 proteins were preliminary screened for Major Histocompatibility Complex (MHC) class II affinity and promiscuity using ProPred program. In addition, subcellular localization and host protein homology was analyzed. From these analyses, 23 MAP proteins were selected for a more accurate inmunoinformatic analysis (i.e. T cell and B cell epitopes analysis) and for homology with mycobacterial proteins. Finally, eleven MAP proteins were identified as potential candidates for further immunogenic evaluation: six proteins (MAP0228c, MAP1239c, MAP2232, MAP3080, MAP3131 and MAP3890) were identified as presenting potential T cell epitopes, while 5 selected proteins (MAP0232c, MAP1240c, MAP1738, MAP2239 and MAP3641c) harbored a large numbers of epitopes predicted to induce both cell- and antibody-mediated immune responses. Moreover, immunogenicity of selected epitopes from MAP1239c were evaluated in IFN-γ release assay. In summary, eleven M. avium subsp. paratuberculosis proteins were identified by in silico analysis and need to be further evaluated for their immunodiagnostic and vaccine potential in field and mice model. Highlights: New antigens for diagnosis and vaccine development against MAP are needed. In silico approach on MAP epitope discovery leads eleven protein candidates. Six potential antigens were identified as presenting predicted T cell epitopes. Five potential antigens were predicted to induce T and B cell immune responses. Immunogenicity of potential epitopes induced IFN-γ release in vitro assay.